COMPARISON OF FREQUENCY OF CAESAREAN SECTION WITH SPONTANEOUS AND INDUCED LABOUR (The Research of Medical Science Review, 2025)
Background: Cesarean section (C-section) rates have been rising globally, often influenced by the mode of labor onset. Understanding the relationship between spontaneous and induced labor and their association with cesarean delivery is vital for improving maternal and fetal outcomes. Aim: To compare the frequency of cesarean sections among women who underwent spontaneous labor versus those who had induced labor. Methods: This cross-sectional study was conducted at the Department of Obstetrics & Gynecology, Khairpur Medical College, Civil Hospital, Khairpur, Khairpur Mirs, from May 2024 to October 2024. A total of 83 pregnant women who met the inclusion criteria were enrolled using a non-probability consecutive sampling technique. Participants were categorized based on whether they experienced spontaneous or induced labor, and the frequency of cesarean sections was recorded for each group. Results: The overall CS rate was 33.7%. Women in the induced labour group had a significantly higher CS rate (48.6%) compared to those in spontaneous labour (22.9%) (p = 0.014). The most common indication for CS was fetal distress (35.7%), followed by failed induction (25%). Maternal complications were slightly higher in the induced group (11.4%) than the spontaneous group (4.2%), while neonatal complications were more frequent in induced labours (17.1% vs. 6.3%). Conclusion: According to the study, the frequency of cesarean sections among the women with induced labor was higher than that among women with spontaneous labor. The results point to the necessity of making knowledgeable selections in preferring labor induction and draw attention to the significance of person-centered strategies of labor control in minimizing unneeded cesarean births.